Possible associations of personality traits representing harm avoidance and self-directedness with medication adherence in Japanese patients with type 2 diabetes - Yoshiko Tominaga; Tohru Aomori; Tomohisa Hayakawa; Nobuhiko Kijima; Donald E. Morisky; Kunihiko Takahashi; Mayumi Mochizuki (BMC, 2018)
Abstract Background Insufficient medication adherence in diabetes patients, of which numbers continue to increase globally, remains a critical issue. Medication adherence is multifactorial and determined by interactions among factors including socioeconomic status, health care team and system, condition, therapy, and patient-specific factors. On the other hand, personality traits have been studied in adherence other than to medication. Using the instruments of Temperament and Character Inventory (TCI), Harm Avoidance (TCI-HA) and Self-directedness (TCI-SD) showed distinguishing associations with adherence of health-related programs. However, few studies have been performed to elucidate psychometric properties related to medication adherence. We investigated how TCI-HA and TCI-SD of patients with diabetes are related to medication adherence. Method A cross-sectional survey was conducted among type 2 diabetes patients recruited at medical institutions or via an online research company. Medication adherence was measured using the 8-item Morisky Medication Adherence Scale (MMAS-8). Personality traits were assessed using the established scales of TCI-HA and TCI-SD. Univariate and multivariate regression analyses of the MMAS-8 scores were performed in addition to assessing demographic and disease characteristics and TCI-HA and TCI-SD. Results A total of 358 responses were analyzed. Multivariate regression analysis of MMAS-8 scores revealed that higher TCI-SD was related to better adherence and experiencing drug-related side effects was related to poor adherence. Aging was significantly associated with better medication adherence in univariate regression analysis but became insignificant in multivariate regression. Conclusions In diabetes patients, the anxiety reflected in TCI-HA tends to lower and the self-control reflected in TCI-SD tends to promote medication adherence. TCI-SD has a greater effect than TCI-HA.